Inhaled beclomethasone/formoterol in idiopathic pulmonary fibrosis: a randomised controlled exploratory study. Issue 4 (14th December 2017) - Wright, Caroline E.; Fraser, Simon D.; Brindle, Kayleigh; Morice, Alyn H.; Hart, Simon P.; Crooks, Michael G.
We hypothesise that inflammation plays a role in idiopathic pulmonary fibrosis (IPF) and that the harm associated with corticosteroid-containing regimens in IPF may relate to local beneficial effects being counterbalanced by deleterious systemic effects [1, 2]. Topical lung delivery could improve the poise between risk and benefit. IPF biomarker improved by ICS/LABA http://ow.ly/CHub30gzHry